Dermatoglyphic findings in congenital clubfoot - (:unkn) unknown (My University, 2000)
The dermatoglyphics of the hand of 33 male and 17 female, a total of 50 patients with congenital clubfoot deformity (CFD) were compared with those of 250 male and 250 female, a total 500 control cases. The most remarkable dermatoglyphic findings observed in CFD were the decreased frequency of ulnar loops and the increased frequency of whorls on all fingers, the decreased frequency of ulnar loops on the left long finger and ring finger and the right thumb, long finger and little fingers, the increased frequancy of whorls on the left long finger and the right thumb, long finger, ring finger and little fingers, the decreased frequency of palmar IV loops and the increased frequency of Ĥ loops and t triradii and the decreased frequency of plantar Î and V̂ loops and the increased frequency of the p and p" triradii on the soles.
Keywords: Clubfoot; Dermatoglyphics